ANALISA SIFAT FISIK DAN KIMIA BRIKET ARANG DARI CAMPURAN TANDAN KOSONG AREN (Arenga pinnata Merr) DAN CANGKANG KEMIRI (Aleurites trisperma) - Hari Wahyu Basuki; Yuniarti Yuniarti; Fatriani Fatriani (Universitas Lambung Mangkurat, 2020)
The waste of candlenut shells and empty sugar palm bunches has considerable potential and can be used as raw material for charcoal briquettes. This study aims to analyze the properties of charcoal from a mixture of candlenut shells and palm sugar bunches on the physical properties of the charcoal briquettes produced. To determine the effect of the mixture of candlenut charcoal shells and sugar palm empty fruit bunches, treatment of 100% candlenut shells, 100% sugar palm empty bunches, 75% candlenut shells + 25% sugar palm empty bunches, 75% empty sugar palm bunches + 25% candlenut shells, 50% candlenut shell + 50% sugar palm bunches, the adhesive used is tapioca flour. Charcoal briquettes produced by the water content ranged from 7.568% - 11.734%, density 0.520g / cm³ - 0.604g / cm abu, the average ash content ranged from 15% - 22.666%, flying substance content 43.666% - 52%, bound carbon ranged from 17,335% - 44,098%, and calorific value 3676,86kal / g - 4749,606kal / g. The water content that meets ASTM is found in treatment A (100% hazelnut shell) of 7.568%, other treatments do not meet ASTM standards. Density, ash content, fly substance content, bound carbon and calorific value produced from various treatments none meet the standard.Keywords: Aren empty bunches charcoal briquettes; candlenut shell briquettes; influence of physical and chemical properties; ASTM standards